Ovotesticular disorder of sex development in a 46 XY adolescent: a rare case report with review of the literature - Koui Bbs; Abouna Ad; Toukilnan Djiwa; Traore B; Kouyate M; Kouame Ke; Aman Na (BMC, 2023)
Abstract Introduction : Ovotestis is a rare cause of sexual ambiguity characterized by the presence in a patient of both testicular and ovarian tissue, leading to the development of both male and female structures. We report a case of ovotestis diagnosed in an adolescent, with a review of the literature. Case Report A 15-year-old patient presented with a right scrotal swelling associated with gynecomastia. Histology showed a juxtaposition of ovarian stroma with ovarian follicle and seminiferous tubules. Karyotype revealed a male subject (XY). We have therefore retained the diagnosis of ovotesticular disorders of sex development. Conclusion Ovotestis is a rare finding, heterogeneous in its genetic etiology and clinical presentation. While many patients are diagnosed during infancy or childhood, we presented a case diagnosed in a 15-year-old adolescent.